Students' Recognition of Concepts of Reflection and Refraction in Multiple Representational Formats - Danilo Jr Tadeo; Junehee Yoo (Universitas Muhammadiyah Makassar, 2022)
A complete understanding of reflection and refraction is achieved when students can recognize the concepts in different representations such as verbal, mathematical, and ray diagrams. The study explores the inconsistencies and difficulties in the students' understanding of image formation by mirrors and lenses. The primary researcher analyzed data on students' performance on a 20-item test consisting of verbal, mathematical, and ray diagram representation items. Two hundred thirty-one (231) grade 10 students took the test after 52-hour instructions on light reflection and refraction. The test results reveal a recognition of the concepts of image formation better in verbal representation by the students. In addition, chi-square results implied that students had drawn the rays in their ray diagrams of spherical mirrors based on their equivalent understanding of the situation in verbal representation. Inconsistencies in their knowledge of reflection by mirrors and refraction by lenses were identified by the differences in the students' responses to verbal and ray diagram representations and supported by the number of students who correctly answered the same items in these two representations. Inconsistencies with the mirror or lens equation were also determined by comparing the results of the items in mathematical representation. Students are found to have difficulties applying the mirror or lens equation and ray-tracing method in problem situations. These observed inconsistencies and problems in multiple representations imply that students have a poor and incomplete understanding of the topic under study.